Analyzing the reality of green finance within the global finance index An analytical study - Shaker Mohsen Saber; Haider Hamza Judy (Journal of Madenat Alelem University College, 2023)
The research aims to analyze the data and information related to the issuance of green bonds globally and their source is the Global Finance Index. This indicator is issued by the Green Finance Council (GGFC), which was established in (2017) for the purpose of bringing together the main global and regional associations and other stakeholders involved in green finance in one council, with the aim of covering a variety of financial products, especially green bonds and loans. The Global Green Finance Index is a measure of the quality and depth of green financial products through global financial centers. It is an indicator approved by the United Nations. This indicator seeks to use advanced statistical techniques to bridge the current data gap. It combines quantitative indicators and estimates of specialists and experts in financial instruments. Collecting data for the index continuously and it is updated twice a year, so it is sensitive to realistic changes in the international political and economic environment. Fossil fuels and their carbon emissions. It has also been shown that there is increasing confidence in the development of green finance in all regions of the world, so the ratings of green finance have increased in almost all centers in terms of depth and quality, due to the global trend towards climate, which opened the way for most countries to adopt the philosophy of reducing emissions.